Une extension du théorème de composition de Horwitz sur les séries de puissances avec des exposants complexes - Popov, V. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. П. Попов. Обобщение композиционной теоремы Гурвица на общие степенные ряды с комплексными показателями V Popovas. Hurvico kompozicijos teoremos apibendrinimas eilučių su kompleksiniais rodikliais atveju